THU0340 Adrenal insufficiency during glucocorticoid treatment in patients with polymyalgia reumatica or giant cell arteritis. (15th June 2017) - Laursen, T; Locht, H; Jensen, B; Borresen, S; Feldt-Rasmussen, U; Hilsted, L; Bartels, EM
Abstract : Background: Adrenal insufficiency secondary to long-term systemic glucocorticoid treatment is a well-recognized problem. However, the extent and prevalence of this phenomenon has not been thoroughly explored. Objectives: To investigate the prevalence of adrenal insufficiency in patients with polymyalgia reumatica (PMR) and giant cell arteritis (GCA) during treatment with low doses of prednisolone (<10mg/day) assessed by the adrenal response to a 250 microgram Synachten® test. To explore whether potential adrenal insuffiency was associated with duration of steroid treatment. Methods: Outpatients were examined when prednisolone doses were between 2.5 and 10 mg/day for >6 months. Adrenal function was evaluated after a 48-hour pause of prednisolone, using a 250 μg Synachten® (ACTH) test where plasma cortisol levels were measured at baseline and 30 minutes after Synacthen injection. Adrenal insufficiency was defined as plasma cortisol <420 nmol/l after 30 minutes according to the validated Roche Elecsys®Cortisol II assay. Accummulated doses of prednisolone for the individual patients were calculated. A multiple regression analysis was used to test for an association between the plasma cortisol after 30 minutes and the accumulated dose of prednisolone. Results: Forty-eight patients (35 women) completed the Synachten® test. Seven (14.6%) patients exhibited adrenal insufficiency. Median age was 74 years (Range: 57–89 years). Median accumulated dose was 3.402 mg (Range: 820–21.200mg). Median plasma cortisol after 30 minutes was 562 nmol/l (Range: 92–989 nmol/l). In patients with adrenal insufficiency, median plasma cortisol was 122 nmol/l (Range: 56–275 nmol/l) at baseline and 207 (Range: 92–420 nmol/l) after 30 minutes. In patients without adrenal insufficiency, median plasma cortisol was 359 (Range: 9–710 nmol/l) at baseline and 584 nmol/l (Range: 429–989 nmol/l) after 30 minutes. Accumulated doses of prednisolone did not differ in patients with and without adrenal insufficiency (p=0.49). Plasma cortisol after 30 minutes was not associated with accumulated dose of prednisolone (estimate −0.01, 95% CI: −0.02 to 5.39, p=0.06), when adjusting for sex and age. Conclusions: Iatrogenic adrenal insufficiency was prevalent among patients with PMR or GCA treated with low dose prednisolone. Adrenal function was not associated with the accumulated dose of prednisolone, or the duration of steroid treatment. A Synacthen® test is a valuable tool to evaluate the adrenal function, when steroid treatment is tapered in these patients. Latent symptoms of adrenal insufficiency may explain why some patients are reluctant to discontinue steroid treatment even after the inflammatory condition has gone into remission. Disclosure of Interest: None declared